An Action Research Investigation Into The Impact Of The Probing Promting Learning Model On Fourth-Grade Students' Understanding Of Growth And Development In Living Organisms - Liana Liana; Asnita Hasibuan (Journal on Education, 2024)
This Classroom Action Research (CAR) studies the influence of implementing the Probing Promting learning paradigm on fourth-grade students' knowledge of science topics, particularly in the context of the growth and development of living things. The study employs a cyclic approach led by the Kemmis and Taggart model, encompassing planning, acting, observing, and reflecting. Data gathering includes test scores, teacher and student observation percentages, and evaluations of teacher and student activities. The results reveal a substantial positive link between the Probing Promting learning approach and increased academic achievement. Test results, starting at an average of 54.48 in the pre-cycle, rapidly improved to 83.70 in Cycle II. The use of the methodology also positively increased instructor and student observation percentages, reaching 96.43% and 92.85%, respectively, in Cycle II. Observations of instructor and student actions, undertaken by two observers, demonstrated constant progress across cycles. The Probing Promting model's repeated application led to enhanced teaching tactics and increased student involvement. The research suggests that the Probing Promting learning paradigm is effective in boosting science instruction for fourth-grade kids, giving a helpful tool for instructors. The excellent outcomes underline the necessity of selecting proper teaching approaches to establish a friendly and effective learning environment. Further research in varied educational settings may give more insights, adding to the continuing improvement of scientific teaching approaches.